Analysis of Financial Distress Using Financial and Non-Financial Indicators with the Altman Z-Score, Grover, and Springate Approaches - Euis Mufahamah; Anita; Siti Musyafa'ah (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze financial distress using financial and non-financial indicators in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research method used is a quantitative approach with secondary data in the form of the company's annual financial statements, which is analyzed by regression panel data. The measurement of financial distress prediction in this study used the Springate model. Based on the results of the model selection test, the most appropriate approach to use is the Common Effect Model (CEM). The results of hypothesis testing showed that Leverage, Net Profit Margin, and Current Ratio had a significant effect on financial distress, while audit committees and institutional ownership had no effect on financial distress. Simultaneously, all independent variables have been shown to have a significant effect on financial distress. The implications of this study are expected to be a consideration for company management in improving the efficiency of financial management as well as for investors in assessing the level of financial health and risk of financial distress before making investment decisions.